La capacità visiva dello spettatore. Qualche riflessione sulla dimensione socioculturale del guardare - Ugenti, Elio (Scenari, 2021)
The “visual capacity” of a spectator, of a subject in front of an image, depends both on fisiological elements and on socio-cultural ones. Starting from the idea of a “social costruction of the gaze”, discussed by W.J.T. Mitchell, and proceeding with the well known assumptions about the “period eye” by Michael Baxandall, this article will focus on the comprehension of the decoding processes of an image by an historically and culturally situated individual. Referring to this theoretical basis, Noël Burch’s thoughts on the relation between the evolution of representational codes (in the cinematic language in particular) and the transformation of the reception resources of the spectator over the time will be taken into consideration. Finally, we will use this methodological approach to analyse the contemporary interaction between cinema and new digital media, and to assess the ways in which the socio-cultural context connects with the production and reception of these “new” images.